Tanggapan, Topik, dan Sentimen dalam Komentar pada Video YouTube Abel Cantika “Tampilan Makeup Favorit!” - Viola Normayanti; Muh. Akbar; Arianto (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2026)
This study analyses netizen interactions with a YouTube video titled “Favourite Makeup Look!”. Favourite Makeup Products' uploaded by the Abel Cantika channel. The purpose of this study is to understand netizen interaction patterns and the sentiment contained in the comments, as well as to identify the level of toxicity in the video's comment section. The method used is a qualitative case study approach using Communalytic.org software. The findings of this study indicate that this video received very positive responses from the audience, with 93.88% of comments in English and 91.02% of comments in other languages showing positive sentiment. Comment activity experienced a significant surge in the period from late March to early April 2025, indicating potential virality. However, interactions after the peak tended to decline and were more one-sided, with few replies given. In addition, the average toxicity score was very low, indicating that the comments in this video tended to be safe and free from harmful content. The significance of these findings shows that the video was able to create a positive and safe space for interaction, but did not encourage further conversation or in-depth discussion